2019
DOI: 10.1039/c9ra01345h
|View full text |Cite|
|
Sign up to set email alerts
|

A clinical and computational study on anti-obesity effects of hydroxycitric acid

Abstract: Hydroxycitric acid (HCA), a major active ingredient of Garcinia cambogia extracts, is known to suppress body weight gain and fat synthesis in animals and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…206 Importantly, several ACLY inhibitors including ETC-1002 (Phase 2/3 clinical trials) and hydroxycitrate (randomised control trials) have shown high efficacy in lowering low-density lipoprotein-cholesterol and good tolerability in patients with cardiovascular disease and type 2 diabetes (Table 1), thus indicating that ACLY inhibition could represent a well-tolerated therapeutic strategy. [207][208][209][210][211] There is considerable interest in ACLY as a target for anticancer drugs; however, clinical trial studies in this context are far more limited when compared with dyslipidaemia cases. Nevertheless, there is a plethora of preclinical evidence to support the integral role of ACLY in tumorigenesis and the potential clinical benefits for its selective inhibition.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…206 Importantly, several ACLY inhibitors including ETC-1002 (Phase 2/3 clinical trials) and hydroxycitrate (randomised control trials) have shown high efficacy in lowering low-density lipoprotein-cholesterol and good tolerability in patients with cardiovascular disease and type 2 diabetes (Table 1), thus indicating that ACLY inhibition could represent a well-tolerated therapeutic strategy. [207][208][209][210][211] There is considerable interest in ACLY as a target for anticancer drugs; however, clinical trial studies in this context are far more limited when compared with dyslipidaemia cases. Nevertheless, there is a plethora of preclinical evidence to support the integral role of ACLY in tumorigenesis and the potential clinical benefits for its selective inhibition.…”
Section: Therapeutically Exploiting Fatty Acid Metabolism In Cancermentioning
confidence: 99%
“…The major organic acid in the fruit rind of Garcinia is hydroxycitric acid (HCA), a proven natural antiobese agent (Onakpoya et al, 2011). Tomar et al (2019) reported the anti-obesity effects of HCA with the help of clinical data and metabolic model analysis. They found that HCA treatment reduced body weight gain and fat accumulation in obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Study results showed that there was significant reduction in the body weight, serum triglycerides, HDL, and LDL levels. The hydroxy citric acid treatment may reduce the body weight gain and fat deposits in obese patients [67]. The enzymatic activities and proteins levels of the citrate synthase were reduced in obese patients in another study of human omental adipose tissue [68].…”
Section: Role Of Citrate In Fatty Liver Diseasementioning
confidence: 97%